ENGLISH LANGUAGE EDUCATION STUDENTS AND THEIR PERCEPTIONS REGARDING THE VARIOUS ACCENTS OF THE ENGLISH LANGUAGE - Pradana, Harsya Danang (Journal of Foreign Language Teaching and Learning, 2019)
This study intends to identify the perceptions of English Language Education students from a pre-determined private university in Yogyakarta regarding the English language and its accents. Many English Language Education students prefer accents from English-speaking countries to accents from countries that use English as a second or foreign language. However, many of them may not be able to speak in accents from the former category. The current study aims to find the reasons for this phenomenon, and whether or not having a preferred accent helps them learn the English language. The research uses qualitative design to search for more detailed answers and uses a custom-made interview as a research instrument. To that end, the researcher enlists five students of English Language Education from this private university as participants in this study, where they receive questions about their accents, view on accents, and whether or not having an accent has helped them learn English. The results of the research indicated that while the students have a mixed view of accents and use various accents themselves, having a familiar accent to use when learning English has helped them learn the language better. Being familiar with an accent and mimicking the source of language input gives the participants an easier time when learning the English Language.